2012
DOI: 10.1007/s11739-012-0813-x
|View full text |Cite
|
Sign up to set email alerts
|

Emergency management of puerperal breast abscess

Abstract: A 38-year-old woman, who was 1 month postpartum, presented with left breast pain. The patient reported a 5-day history of stabbing left breast pain, erythema, and tenderness. She had been breast feeding and pumping breast milk without difficulty, but recently noted blood, mucous, and purulent material within the pumped milk. The patient denied fevers, chills, breast trauma, a palpable mass, or right breast abnormalities. Ultrasound of the left breast demonstrated a 4.7 9 2.1 cm complex fluid collection with as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…The most common bacterium found in breast abscess secretion culture was Staphylococcus aureus, which coincides with our findings 15, 23-28 . Various other studies also reported MRSA in breast abscess secretion culture which is similar to our study 25,27 . A lactational breast abscess is usually bacterial in etiology and can be effectively managed with oral antibiotics.…”
Section: Discussionsupporting
confidence: 91%
“…The most common bacterium found in breast abscess secretion culture was Staphylococcus aureus, which coincides with our findings 15, 23-28 . Various other studies also reported MRSA in breast abscess secretion culture which is similar to our study 25,27 . A lactational breast abscess is usually bacterial in etiology and can be effectively managed with oral antibiotics.…”
Section: Discussionsupporting
confidence: 91%
“…20 It is generally recommended that lactating women continue to evacuate the affected breast by means of breastfeeding or pumping to promote expulsion of milk from the affected ducts and prevent stasis, which would favor abscess formation. 21 Infections associated with piercing of the nipple may present either early or late, and may be attributable to other organisms, such as β-hemolytic Streptococcus and Actinomyces, making culture and sensitivity of the causative organism of particular importance in this population. 22 Spontaneous nonpuerperal abscesses in adults are associated with smoking and diabetes, 23 conditions that also affect adolescents.…”
Section: Infectionmentioning
confidence: 99%
“…In the context of maternal and infant health, many studies have described incidence and transmission of communityassociated and healthcare-associated strains, in addition to recommended antibiotic regimens, invasive and noninvasive management, and prevention strategies including decolonization (Saiman et al, 2003;Fortunov et al, 2007;Alsubaie et al, 2012;Jahanfar et al, 2013;Sheffield, 2013). With respect to mastitis specifically, most reports relate to incidence and treatment of S. aureus maternal infection (Branch-Elliman et al, 2012;Chick et al, 2012;Iatrakis et al, 2013;Perez et al, 2013) and, to a lesser degree, subsequent transmission of infection to (mostly pre-term and neonatal) infants (Behari et al, 2004;Gastelum et al, 2005;Kayiran et al, 2014). Mastitis in children is less common and is largely related to neonates and pubescent/ postpubescent age groups (Faden, 2005).…”
Section: Introductionmentioning
confidence: 99%